A multi-tracer approach for understanding the functioning of heterogeneous phreatic coastal aquifers in humid tropical zones. Issue 4 (12th March 2021) - Campillo, Ana; Taupin, J. D.; Betancur, T.; Patris, N.; Vergnaud, V.; Paredes, V.; Villegas, P.
ABSTRACT: In many areas around the world, phreatic coastal aquifers are vulnerable to contamination and saltwater intrusion. This study aims to explore the hydrodynamic functioning of the coastal phreatic aquifer of the Urabá region, Colombia, based on the identification of hydrogeochemical processes and groundwater residence and transit times. Hydrodynamic data showed a fast response of the piezometric levels to precipitation with a maximum time lag of 48 h. Mean annual recharge was estimated at 19% with respect to precipitation. Another recharge mode is linked to infiltration from surface water, according to the hydrodynamic results. The main geochemical process identified is hydrolysis due to dissolved carbon dioxide, inducing silicate weathering and resulting in predominant HCO3 -Ca-Mg facies. Monitoring of δ 18 O and δ 2 H compositions combined with 3 H, 14 C, chlorofluorocarbons (CFCs) and SF6 contents showed a fast recharge in the aquifer. Groundwater dating indicates recent waters mixed with older (>40 years) waters.